ANALYSIS AND IDENTIFICATION OF NEW STUDENT ACCEPTANCE SYSTEM WITH EQUAL WIDTH INTERVAL DISCRETIZATION TECHNIQUE IN K-MEANS CLUSTERING METHOD (CASE STUDY: SMA NEGERI 9 MEDAN) - Rahmad, Sofyan; Zarlis, Muhammad; Situmorang, Zakarias (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The admission of new students is the first gate that students and schools must pass through in screening educational objects. It is an important event for a school because it is the starting point that determines the smooth running of a school's work. The new student admission system (PPDB) has been implemented by many schools. One of these schools is SMA Negeri 9 Medan. The Equal-width interval Discretisation technique is the simplest discretization method that divides the range of observed values on each feature/attribute, variable k is a parameter provided by the user. This study will calculate what criteria are used to select new students at the school. The criteria used such as the distance of the new student's residence area to the school, academic achievement, and others are then calculated and as a support, Rapidminer 10.1 software is used. The results of data testing and cluster data will be processed to be considered as recommendations for schools and new students at the school